1973
DOI: 10.2307/3573794
|View full text |Cite
|
Sign up to set email alerts
|

Diamide: A New Radiosensitizer for Anoxic Cells

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1977
1977
2004
2004

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Thiol-containing compounds have often been proposed as protective agents against free-radical-mediated tissue injury. Indeed, there is now considerable evidence that cells deprived of GSH, as the result of a mutation or because of the presence of exogenous agents such as diamide, are more sensitive to the damaging action of ionizing radiation (Edgren et al, 1970;Harris & Power, 1973). The most common mechanism proposed for such a protective action is the repair of an initial lesion Cyt(Il).c Scheme 1.…”
Section: Discussionmentioning
confidence: 99%
“…Thiol-containing compounds have often been proposed as protective agents against free-radical-mediated tissue injury. Indeed, there is now considerable evidence that cells deprived of GSH, as the result of a mutation or because of the presence of exogenous agents such as diamide, are more sensitive to the damaging action of ionizing radiation (Edgren et al, 1970;Harris & Power, 1973). The most common mechanism proposed for such a protective action is the repair of an initial lesion Cyt(Il).c Scheme 1.…”
Section: Discussionmentioning
confidence: 99%
“…the sulfhydryl oxidizing agent diamide there is a synergistic effect on the radiation response that is greater than that obtainable by either agent alone (31,32). Harris and Power reported a lower survival at both 800 and 1200 rads for anoxic cells irradiated in the presence of diamide and nifuroxime (a nitrofuran) than was observed for either sensitizer alone (32). Similarly, Chapman et al (33) showed that diamide plus NF-269, another nitrofuran, sensitized to a greater degree than that of either agent alone, and more than oxygen.…”
Section: Mechanism Of Action Of Hypoxic Cell Radiosensitizersmentioning
confidence: 99%
“…The pretreatment effects with misonidazole (25,35) and the combination studies with the thiol oxidant diamide (31)(32)(33)(34) suggest that endogenous reducing species are important in the overall mechanism of radiation damage and repair. As mentioned previously, the reaction of the DNA radicals with hydrogen donor or reducing substrates will result in chemical repair of the radiation damage.…”
Section: Hydrogen Donors and Chemical Repair Of Radiation Damagementioning
confidence: 99%
“…Cellular radiosensitivity is affected by the presence of endogenous intracellular thiols. Oxydation of these thiols by diamide (20,21) renders the cells more sensitive. Monoethyl and diethyl esters of glutathione had the capacity to provide some protection of normal and buthionine sulfoxime pretreated cells against X-…”
Section: Nitroimidazolesmentioning
confidence: 99%